Learning Experiences of Adults Mentoring Socially Excluded Young People: Issues of Power and Gender - Helen Colley (Adult Education Research Conference, 2004)
Adult educators have not as yet investigated the vast movement of adults who mentor socially excluded youth. But these mentors are adult learners too. Their experiences suggest that mentoring – in any context – may entail the ‘toxic’ learning of emotional labour. More attention should be paid to their training from a perspective of social justice.